Peraturan Mahkamah Agung No.3 Tahun 2021: Bukti Mahalnya Keadilan di Indonesia - Purba, M Hadyan Yunhas; Sirait, Ningrum Natasya; Siregar, Mahmul; Dedi Harianto (Jurnal Ilmiah Penegakan Hukum, 2023)
Legal remedies for objections to the decision of the Business Competition Supervisory Commission ("KPPU") submitted to the Commercial Court (formerly the District Court) are the legal rights of the reported business actor who does not accept the decision. This right has been guaranteed in Law No. 5 of 1999 concerning the Prohibition of Monopolistic Practices and Unfair Business Competition ("UU No. 5/1999") and Law No. 11 of 2020 concerning Job Creation ("Law No. 11/2020"). The rights guaranteed by the two regulations are human rights as regulated in Article 28D paragraph (1) of the 1945 Constitution of the Republic of Indonesia ("1945 Constitution"), where these rights must, of course, be respected and upheld. This type of research is normative juridical research, which involves taking inventory of laws and regulations, journals, legal principles, encyclopedias, and other literature to be analyzed qualitatively. The results obtained made it known that the norms contained in Article 4 paragraph (1) letter D of Supreme Court Regulation Number 3 of 2021 concerning Procedures for Filing and Examination of Objections to Decisions of the Commission for the Supervision of Business Competition at the Commercial Court ("Perma No.3/2021") became an obstacle for the reported business actor in filing an objection against the KPPU's decision. This is not appropriate and is contrary to the concept of a rule of law.